Humoral Response to the Fourth BNT162b2 Vaccination and Link Between the Fourth Dose, Omicron Infection, and Disease Severity in Renal Transplant Recipients. Issue 1 (8th December 2022) - Hod, Tammy; Ben-David, Aharon; Mor, Eytan; Olmer, Liraz; Halperin, Rebecca; Indenbaum, Victoria; Beckerman, Pazit; Doolman, Ram; Asraf, Keren; Atari, Nofar; Benjamini, Ohad; Lustig, Yaniv; et al.
Abstract : Background: The effectiveness of the fourth BNT162b2 vaccination in reducing the rate and severity of coronavirus disease 2019 (COVID-19) caused by the Omicron variant in renal transplant recipients (RTRs) is unknown. Methods: Interviews were conducted with 447 RTRs regarding the status and timing of the fourth vaccination, prior vaccinations, and preceding COVID-19 infection. RTRs with polymerase chain reaction–confirmed COVID-19 infection from December 1, 2021, to the end of March 2022 were considered to have been infected with the Omicron variant and were interviewed to determine their disease severity. In a subgroup of 74 RTRs, the humoral response to the fourth dose was analyzed. In 30 RTRs, microneutralization assays were performed to reveal the humoral response to wild-type, Delta, and Omicron variant isolates before and after the fourth dose. Results: Of 447 RTRs, 144 (32.2%) were infected with the Omicron variant, with 71 (49.3%) of the infected RTRs having received the fourth vaccine dose. RTRs who did not receive the fourth dose before the infection had more serious illness. In a subgroup of 74 RTRs, the fourth dose elicited a positive humoral response in 94.6% (70/74), with a significant increase in geometric mean titer for receptor-binding domain immunoglobulin G and neutralizing antibodies ( P  < 0.001). The humoral responses to the Omicron variant before and after the fourth dose were significantly lower than the responses to the wild-type and the Delta variants. Conclusions: Overall, the fourth BNT162b2 dose was effective in reducing the rate and severity of Omicron disease in RTRs, despite the reduced humoral response to the variant. Abstract :